O processo de construção da identidade e do estado-nação em Cabo Verde - Paulo Madeira, João (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The construction of the nation-state in Cape Verde comes from a sociohistoric base that began with the discovery and settlement of the archipelago islands. This article intends to understand the processes that were involved in the formation of identity and subsequently, the construction of the nation-state. The process includes on the one hand, the birth of mestizo and the utterance of the Cape Verdean Creole language, and on the other hand, cultural manifestations that culminate with national independence in 1975 and subsequently, with the political opening process in 1990, and the institutional consolidation of democracy.